Staff experiences of enhanced recovery after surgery: systematic review of qualitative studies. Issue 2 (12th February 2019) - Cohen, Rachel; Gooberman-Hill, Rachael
Abstract : Objectives: To conduct a systematic review of qualitative studies which explore health professionals' experiences of and perspectives on the enhanced recovery after surgery (ERAS) pathway. Design: Systematic review of qualitative literature using a qualitative content analysis. Literature includes the experiences and views of a wide range of multidisciplinary team and allied health professional staff, to incorporate a diverse range of clinical and professional perspectives. Data sources: PsycINFO, Medline, CINAHL and PubMed were searched in May 2017. Eligibility criteria for selecting studies: The searches included relevant qualitative studies across a range of healthcare contexts. We included studies published from 2000 to 2017, as an appropriate time frame to capture evidence about ERAS after implementation in the late 1990s. Only studies published in the English language were included, and we included studies that explicitly stated that they used qualitative approaches. Data extraction and synthesis: Literature searches were conducted by the first author and checked by the second author: both contributed to the extraction and analysis of data. Studies identified as relevant were assessed for eligibility using the Critical Appraisal Skills Programme guidance. Results: Eight studies were included in the review, including studies in six countries and in four surgical specialties. Included studies focus on health professionals' experiences of ERAS before, during and after implementation in colorectal surgery, gastrointestinal surgery, abdominal hysterectomy and orthopaedics. Five main themes emerged in the analysis: communication and collaboration, resistance to change, role and significance of protocol-based care, and knowledge and expectations. Professionals described the importance of effective multidisciplinary team collaboration and communication, providing thorough education to staff and patients, and appointing a dedicated champion as means to implement and integrate ERAS pathways successfully. Evidence-based guidelines were thought to be useful for improvements to patient care by standardising practices and reducing treatment variations, but were thought to be too open to interpretation at local levels. Setting and managing 'realistic' expectations of staff was seen as a priority. Staff attitudes towards ERAS tend to become more favourable over time, as practices become successfully 'normalised'. Strengths of the review are that it includes a wide range of different studies, a variety of clinical populations, diversity of methodological approaches and local contexts. Its limitation is the inclusion of a small number of studies, although these represent six countries and four surgical specialties, and so our findings are likely to be transferable. Conclusions: Staff feel positive about the implementation of ERAS, but find the process is complex and challenging. Challenges can be addressed by ensuring that multidisciplinary teams understand ERAS principles and guidelines, and communicate well with one another and with patients. Provision of comprehensive, coherent and locally relevant information to health professionals is helpful. Identifying and recruiting local ERAS champions is likely to improve the implementation and delivery of ERAS pathways. PROSPERO registration number: CRD42017059952